One-Year Follow-Up of the Effectiveness of Cognitive Behavioral Group Therapy for Patients’ Depression: A Randomized, Single-Blinded, Controlled Study - Kai-Jo Chiang; Tsai-Hui Chen; Hsiu-Tsu Hsieh; Jui-Chen Tsai; Keng-Liang Ou; Kuei-Ru Chou (The Scientific World Journal)
The aim of the study was to investigate the long-term (one year) effectiveness of a 12-session weekly cognitive behavior group therapy (CBGT) on patients with depression. This was a single-blind randomized controlled study with a 2-arm parallel group design. Eighty-one subjects were randomly assigned to 12 sessions intervention group (CBGT) or control group (usual outpatient psychiatric care group) and 62 completed the study. The primary outcome was depression measured with Beck Depression Inventory (BDI-II) and Hamilton Rating Scale for Depression (HRSD). The secondary outcomes were automatic thoughts measured by automatic thoughts questionnaire (ATQ). Both groups were evaluated at the pretest (before 2 weeks), posttest (after 12 therapy sessions), and short- (3 months), medium- (6 months), and long-term (12 months) follow-up. After receiving CBGT, the experimental group had a statistically significant reduction in the BDI-II from 40.30 at baseline to 17.82 points at session eight and to 10.17 points at postintervention (P<0.001). Similar effects were seen on the HRSD. ATQ significantly decreased at the 12th session, 6 months after sessions, and 1 year after the sessions ended (P<0.001). We concluded that CBGT is effective for reducing depression and continued to be effective at 1 year of follow-up.